A CAUSAL RELATIONSHIP FACTORS INFLUENCING TO SELF - MANAGEMENT IN PREVENTING COMPLICATION OF TYPE 2 DIABETES ELDERLY IN THE HEALTH REGION 4 MINISTRY OF PUBLIC HEALTH - Waseeweerasi, Wirasiri (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were 1) to study self-efficacy levels, lifestyle behaviors, health literacy, and self-management in the prevention of complications of type 2 diabetes elderly 2) to examine the congruence of the causal factor model influencing self - management in the prevention of complications of type 2 diabetes elderly 3) to investigate the influence of self-efficacy, lifestyle behaviors, and health literacy towards self-management in the prevention of complications. The multi-stage random sampling technique was used to recruit 672 elderly patients with type 2 diabetes. The research instrument was questionnaires covering 5 parts, the Index of consistency (IOC) of 0.90, and the quality of the instruments of parts 2 - 5 having a fidelity value of 0.92, 0.91, 0.97, and 0.96, respectively. Data were analyzed using mean, percentage, standard deviation, Pearson’s Product Moment Correlation Coefficient, and the Structural Equation Model (SEM). The results showed that self - management, self-efficacy, lifestyle behaviors, and health literacy were indicated at a moderate level with a mean 3.74, 3.79, 3.33 and 3.86, respectively. The overall was at a moderate level with a mean of 3.70. The causal factors were consistent and had direct influence on self - management through self-efficacy, and lifestyle behaviors had direct influence on self - management with the influence of 0.39 and 0.57. Health literacy affected through lifestyle behavior indirectly on self-management with the influence of 0.49 and with the total influence of 0.39, 0.49 and 0.57 at a statistical significant level of 0.01. The variance was explained at .88 % (R2 = .88%). Therefore, the public health service agencies should focus on promoting and providing appropriate knowledge on health literacy and lifestyle behaviors.